Els Maia : (episodis de la vida romàntica) - Queirós, Eça de, 1845-1900 (Grans clàssics (Editorial Funambulista), 2012)
Set in Lisbon at the close of the 19th century, this work is both a coming-of-age novel and a passionate romance.